Aerodynamic analysis of a paraglider wing using domain decomposition techniques - Başol, Altuğ Melik. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2007., 2007)
The flow around a curvature tube is investigated using it as a simple 2D model of a paraglider wing based on the similarity between their top views. The solutions are obtained for five different angle of attacks varying from 00 up to 420, for two different radius of curvatures and for two different Reynolds number namely for Re=80 and for Re=160. Two non-matching overlapping domains are used. The flow at these domains is solved separately and the solutions are transferred into each other using the alternating multiplicative Schwarz technique. With the aid of this technique a solver is developed which is capable of solving the flow around various forms of the tube and at different angle of attacks without making any modifications in the outer boundaries and without using grid generation. Newton's methods combined with three different Krylov sub-space solvers are applied. Implementing also Jacobi, symmetric Gauss-Seidel (SGS) and incomplete LU decomposition (ILU(0)) preconditioners into the solvers their effects on the convergence behavior are investigated. It is observed that the ILU(0) has a superior effect on the convergence behavior than the others have. However, its unavailability for the matrix free algorithms makes SGS preconditioned inexact Newton's method a better option as a solver because of its low storage load and low code development period.|Keywords: Newton's method, Krylov solvers, overlapping domain, preconditioners
Keywords: Newton-Raphson method.; Decomposition method.